SPE International Conference on Health, Safety, and Environment 2014
DOI: 10.2118/168449-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Restoration in the Vicinity of Oil and Gas Facilities: Lessons Learned from a Large Scale Project

Abstract: Mangroves are critical ecosystems given their key role in conserving biodiversity, protecting coastlines from erosion and supporting coastal resources. They may be impacted by oil and gas activities, either directly or indirectly. Restoring them is therefore of prime importance. In the Mahakam Delta (East Kalimantan, Indonesia), oil and gas exploration and production have been conducted for more than 40 years. This industry has operated in a quasi-pristine area barely affected by human activities until the mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…In Indonesia, in the period between 1980 and 2003, characterized by weak governance of the aquaculture sector (Ilman et al 2016), thousands of hectares of coastal zone were transformed into a mosaic of aquaculture ponds, of which about 250,000 ha have remained disused ever since (Gusmawati et al this issue). The scale of the conversion is particularly visible in large areas like the Mahakam delta covering about 75,000 km² in East Kalimantan, Borneo Island (Dutrieux et al 2014). Anyone using Google Earth, with its high-resolution satellite images, can see and understand the scale of the impact of aquaculture on such coastal areas.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, in the period between 1980 and 2003, characterized by weak governance of the aquaculture sector (Ilman et al 2016), thousands of hectares of coastal zone were transformed into a mosaic of aquaculture ponds, of which about 250,000 ha have remained disused ever since (Gusmawati et al this issue). The scale of the conversion is particularly visible in large areas like the Mahakam delta covering about 75,000 km² in East Kalimantan, Borneo Island (Dutrieux et al 2014). Anyone using Google Earth, with its high-resolution satellite images, can see and understand the scale of the impact of aquaculture on such coastal areas.…”
Section: Introductionmentioning
confidence: 99%
“…Selisih nilai dimungkinkan oleh aktivitas pembukaan lahan tambak yang tidak hanya di hutan mangrove tetapi juga lahan non hutan mangrove atau di area tanah timbul. Sebagai wilayah delta, tingkat sedimentasi di Delta Mahakam cenderung tinggi sehingga penambahan daratan dapat terus terjadi dan menimbulkan perluasan lahan mangrove secara alami (Dutrieux et al, 2014). Hal ini dapat terlihat dengan bertambahnya luas wilayah studi selama periode pengamatan (Tabel 1).…”
Section: A Kondisi Hutan Mangrove DI Deltaunclassified
“…Pada tahun 2004 (Fase 3), mangrove kembali beregenerasi (recovery) baik secara alami maupun penanaman (plantation), ditandai dengan kenaikan luasan hutan mangrove sekitar 10.000 hektar, meliputi di area ex-tambak, jalur pipa dan tanah timbul, antara tahun 2001-2011 (Dutrieux et al, 2014). Hal ini disebabkan oleh banyaknya tambak yang ditinggalkan (non produktif) karena produksi yang menurun (Bosma, Sidik, van Zwieten, Aditya, & Visser, 2012).…”
Section: A Kondisi Hutan Mangrove DI Deltaunclassified
“…Many studies have reported that mangrove forest plays various ecological functions, such as biodiversity conservation and as coastline protection from erosion (Dutrieux et al, 2014). In addition, mangrove ecosystem is also essential for providing resources for the livelihoods of local communities.…”
Section: Introductionmentioning
confidence: 99%
“…Mahakam Delta has become a notable mangrove ecosystem in East Kalimantan due to its ecological, social and economic importance. Mangrove forests in Mahakam Delta function as feeding source as well as spawning and nursery grounds for aquatic organisms, which become a primary source of local communities' livelihoods (Dutrieux et al, 2014;Sidik, 2010). Zain et al (2014) also noted that mangrove forest in Mahakam Delta has high economic value for communities, from both direct use and indirect use values.…”
Section: Introductionmentioning
confidence: 99%